Brand Ambassador dalam Konsep City Branding di Jakarta - Nasa Yulandari; Jatmiko Jatmiko (Universitas Kristen Indonesia Toraja, 2024)
This study aims to explore and identify significant relationships between Self-city Brand Connection, City Brand Experience, City Brand Satisfaction, and City Brand Ambassadorship Behavior Intention (CB-ABI), as well as the mediating role of City Brand Experience and City Brand Satisfaction. Data collection was conducted using a survey method by distributing questionnaires online, and measurements were taken using Likert scales. The population in this study consisted of residents of Jakarta who had been living in the Jakarta area for 5 years or more, with a total of 120 respondents. This research uses the PLS SEM analysis method. The results of this study indicate that self-city brand connection positively influences city brand experience and city brand satisfaction. However, self-city brand connection does not have an influence on city brand ambassadorship behavior intention. Furthermore, city brand experience has an influence on city brand satisfaction and city brand ambassadorship behavior intention. However, city brand satisfaction does not have an influence on city brand ambassadorship behavior intention. Moreover, city brand satisfaction plays a mediating role in the relationship between Self City Brand Connection and city brand ambassadorship. However, city brand experience does not play a mediating role in the relationship between Self City Brand Connection and city brand ambassadorship. This research provides important insights into the relationships between Self-city Brand Connection, City Brand Experience, City Brand Satisfaction, and City Brand Ambassadorship Behavior Intention among residents living in the Jakarta, Indonesia area.